Asynchronous recruitment of low-threshold motor units during repetitive, low-current stimulation of the human tibial nerve - Dean, Jesse C.; Clair-Auger, Joanna M.; Lagerquist, Olle; Collins, David F. (Frontiers in Human Neuroscience, 2014)
Motoneurons receive a barrage of inputs from descending and reflex pathways. Much of our understanding about how these inputs are transformed into motor output in humans has come from recordings of single motor units during voluntary contractions. This approach, however, is limited because the input is ill-defined. Herein, we quantify the discharge of soleus motor units in response to well-defined trains of afferent input delivered at physiologically-relevant frequencies. Constant frequency stimulation of the tibial nerve (10-100 Hz for 30 s), below threshold for eliciting M-waves or H-reflexes with a single pulse, recruited motor units in 7/9 subjects. All 25 motor units recruited during stimulation were also recruited during weak (<10% MVC) voluntary contractions. Higher frequencies recruited more units (n=3/25 at 10 Hz; n=25/25 at 100 Hz) at shorter latencies (19.4±9.4 s at 10 Hz; 4.1±4.0 s at 100 Hz) than lower frequencies. When a second unit was recruited, the discharge of the already active unit did not change, suggesting that recruitment was not due to increased synaptic drive. After recruitment, mean discharge rate during stimulation at 20 Hz (7.8 Hz) was lower than during 30 Hz (8.6 Hz) and 40 Hz (8.4 Hz) stimulation. Discharge was largely asynchronous from the stimulus pulses with “time-locked” discharge occurring at an H-reflex latency with only a 24% probability. Motor units discharged after the stimulation ended in 89% of trials, although at a lower rate (5.8 Hz) than during the stimulation (7.9 Hz). This work supports the idea that the afferent volley evoked by repetitive stimulation recruits motor units through the integration of synaptic drive and intrinsic properties of motoneurons, resulting in "physiological" recruitment which adheres to Henneman's size principle and results in relatively low discharge rates and asynchronous firing.